Regime transition, value conflicts and the left-right divide at the mass level: the Baltic States and Southern Europe compared - Freire, A.; Kivistik, K. (Communist and Post-Communist Studies, 2016)
By comparing the Baltic States with Greece, Portugal and Spain, we seek to discover whether the type of authoritarian legacy and regime transition has any effect on the way citizens think about the left-right (L-R) divide in new democracies. We argue that while the authoritarian legacy is important, the type of transition and, particularly, the kind of political alliances and party-politicization of issues during the new regime's formative years is more important. Evidence confirms our expectations, even after several cross-validating tests.